Onset of type 1 diabetes mellitus in a patient with infectious mononucleosis - Elena Alexandrovna Kharlashina; Olga Sergeevna Shapoval'yants; Elena Vladimirovna Pekareva; Tatiana Vasil'evna Nikonova (Сахарный диабет)
Diabetes mellitus (DM) is a polygenous multifactor disease that may be triggered by a viral infection that causes death of beta-cells by at least two mechanisms,virus-mediated autoimmunity and direct cell injury. A case of DM1 following infectious mononucleosis is described to illustrate the necessityof a combined approach to the examination of patients and prescription of treatment.